Chief Justice Rose Bird's State of the Judiciary Address at State Bar Annual Meeting - Watkins, Howard::::::::: (1985)
Outgoing State Bar President Burke Critchfield receiving standing ovation with Chief Justice Rose Bird and Incoming State Bar President David Heilbron at lectern